HIV cure research community engagement in North Carolina: a mixed-methods evaluation of a crowdsourcing contest - Allison Mathews; Samantha Farley; Meredith Blumberg; Kimberley Knight; Lisa Hightow-Weidman; Kate Muessig; Stuart Rennie; Joseph Tucker (Elsevier, 2017)
Objectives: The purpose of this study was to evaluate the feasibility of using a crowdsourcing contest to promote HIV cure research community engagement. Methods: Crowdsourcing contests are open calls for community participation to achieve a task, in this case to engage local communities about HIV cure research. Our contest solicited images and videos of what HIV cure meant to people. Contestants submitted entries to IdeaScale, an encrypted online contest platform. We used a mixed-methods study design to evaluate the contest. Engagement was assessed through attendance at promotional events and social media user analytics. Google Analytics measured contest website user-engagement statistics. Text from contest video entries was transcribed, coded and analysed using MAXQDA. Results: There were 144 attendees at three promotional events and 32 entries from 39 contestants. Most individuals who submitted entries were black (n=31), had some college education (n=18) and were aged 18-23 years (n=23). Social media analytics showed 684 unique page followers, 2233 unique page visits, 585 unique video views and an overall reach of 80,624 unique users. Contest submissions covered themes related to the community's role in shaping the future of HIV cure through education, social justice, creativity and stigma reduction. Conclusion: Crowdsourcing contests are feasible for engaging community members in HIV cure research. Community contributions to crowdsourcing contests provide useful content for culturally relevant and locally responsive research engagement.